(untitled) (Gilgameš, 2019)
In this paper, I shall analyse the information we can extract from ancient Greek texts about the training of those citizens chosen to become members of a chorus during the Athenian festivals, as well as the importance to become such. I shall offer a revision of the role of the chorodidaskalos, the person in charge of their instruction, considered, in a certain way, a maestro di canto in the ancient world, in order to determine if we can delimit the professional grounds with which they used to work, from a technical point of view, especially when, in many cases, they had to deal with members not professionally educated for their chorus lines. This panorama will show the importance that the practice of singing within a chorus, principally on an Athenian theatre, implied for those citizens who partook their experience at each festival, and how things were dealt with from the Classical period until we find the phonaskos, a professional trainer of voice that appears in the Greek world from the Roman period onwards.